PENGARUH PROGRAM KOMUNITAS USAHA MIKRO MUAMALAT BERBASIS MASJID (KUM3) BAITULMAAL MUAMALAT TERHADAP PEMBERDAYAAN USAHA MIKRO DI JAKARTA - Bidari Dewanti (Faculty of Economic and Business, 2013)
The purpose of this study was to determine the effect of the program KUM3 Baitulmaal Muamalat to micro-business empowerment in Jakarta. The analysis technique used in this study was the paired t–test, which analyzes the effect of income mustahik between before and after receiving assistance KUM3 program. Based on test results to determine the effectiveness of income before and after getting the financing done by using different test analysis (paired sample t-test) showed that the correlation between income before and after income is very strong and significant, so that the economic empowerment program KUM3 Baitulmaal Muamalat can be said effective. It shows that the financing provided in order to increase revenues micro traders according to customersDOI: 10.15408/etk.v12i2.1912